ETHOS, BOUNDARIES AND PRACTICAL TASKS OF PATRIOTISM - Ślipko, Tadeusz (Studia Philosophiae Christianae, 2020)
The main thesis of this article states that patriotism constitutes a key role in the process of globalization. The author perceives the moral dimension of nation and homeland categories as the validation of such a position. Patriotism, which is not chauvinism, deeply connects with its own nation, as well as homeland, and due to its very nature, should be open to foreigners and other nations.